Mitochondrial BKCa channels contribute to protection of cardiomyocytes isolated from chronically hypoxic rats - Borchert, Gudrun H; Yang, Chengtao; Kolár, Frantisek (American journal of physiology. Heart and circulatory physiology, 2011)
Chronic hypoxia protects the heart against injury caused by acute oxygen deprivation, but its salutary mechanism is poorly understood. The aim was to find out whether cardiomyocytes isolated from chronically hypoxic hearts retain the improved resistance to injury and whether the mitochondrial large-conductance Ca2+-activated K+ (BKCa) channels contribute to the protective effect. Adult male rats were adapted to continuous normobaric hypoxia (inspired O2 fraction 0.10) for 3 wk or kept at room air (normoxic controls). Myocytes, isolated separately from the left ventricle (LVM), septum (SEPM), and right ventricle, were exposed to 25-min metabolic inhibition with sodium cyanide, followed by 30-min reenergization (MI/R). Some LVM were treated with either 30 μM NS-1619 (BKCa opener), or 2 μM paxilline (BKCa blocker), starting 25 min before metabolic inhibition. Cell injury was detected by Trypan blue exclusion and lactate dehydrogenase (LDH) release. Chronic hypoxia doubled the number of rod-shaped LVM and SEPM surviving the MI/R insult and reduced LDH release. While NS-1619 protected cells from normoxic rats, it had no additive salutary effect in the hypoxic group. Paxilline attenuated the improved resistance of cells from hypoxic animals without affecting normoxic controls; it also abolished the protective effect of NS-1619 on LDH release in the normoxic group. While chronic hypoxia did not affect protein abundance of the BKCa channel regulatory β1-subunit, it markedly decreased its glycosylation level. It is concluded that ventricular myocytes isolated from chronically hypoxic rats retain the improved resistance against injury caused by MI/R. Activation of the mitochondrial BKCa channel likely contributes to this protective effect.
Keywords: Cell Survival; Potassium Channel Blockers; indoly; Large-Conductance Calcium-Activated Potassium Channels; Indoles; Mitochondria, Heart; kardiomyocyty; Benzimidazoles; Chronic Disease; reperfuzní poškození myokardu; viabilita buněk; Blotting, Western; krysa rodu Rattus; separace buněk; srdeční mitochondrie; Hypoxia; zvířata; Myocardial Reperfusion Injury; Cells, Cultured; vápníkem aktivované draslíkové kanály s vysokou vodivostí; vápníkem aktivované draslíkové kanály s vysokou vodivostí - beta-podjednotky; Myocytes, Cardiac; benzimidazoly; potkani Wistar; Large-Conductance Calcium-Activated Potassium Channel beta Subunits; Ischemic Preconditioning, Myocardial; hypoxie; L-Lactate Dehydrogenase; glykosylace; Rats, Wistar; Male; chronická nemoc; kultivované buňky; Cell Separation; Rats; Animals; western blotting; ischemické přivykání; L-laktátdehydrogenasa; mužské pohlaví; Glycosylation; blokátory draslíkových kanálů